COMPARATIVE ANALYSIS OF THE 1977 BALTIC SEA LEVEL SYSTEM AND THE EUROPEAN VERTICAL REFERENCE SYSTEM WITHIN THE FRAMEWORK OF TRANSITION TO A UNIFIED EUROPEAN SPATIAL DATA INFRASTRUCTURE - Kovalchuk, Andrii; Shkut, Oleksii (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . Ukraine is preparing for a significant transformation in geodesic support, planning to transition from the outdated Baltic Height System 1977 (BSV-77) to the European Vertical Reference System (EVRS) starting on January 1, 2026. This transition is critically important for modernizing the national geodesic infrastructure, as BSV-77 does not meet contemporary requirements for geospatial data accuracy and limits international integration. The need to implement EVRS is driven by the harmonization of Ukrainian legislation with European standards (INSPIRE Directive) and NATO requiirements, which will ensure the compatibility of geodesic data for the Armed Forces of Ukraine, enhancing their operational capability and effectiveness. M e t h o d s . General scientific methods, including analysis, comparison, synthesis, analogy, and a systemic approach, were utilized in the preparation of this article. A comparative analysis of BSV-77 and EVRS was conducted based on key parameters, including their physical essence, definition of reference surfaces, and methodologies for height measurement. The accuracy of each system, a crucial factor for modern geodetic, cartographic, and engineering-geodetic works, was evaluated. Special attention was given to compliance with international standards, highlighting the integration of EVRS into the global geodetic framework in contrast to the isolated position of BSV-77. The integration of height systems into modern GIS and the application of geoid models were also thoroughly analyzed. R e s u l t s . The research highlights the significant advantages of EVRS over BSV-77 in terms of accuracy, compatibility, and compliance with international standards. The transition to EVRS will enable Ukraine to integrate into a unified European spatial data infrastructure and ensure full compatibility of cartographic and geospatial data with NATO standards, which is of paramount importance for the defense sector. The complexity of data transformation between systems and the necessity of developing reliable algorithms for seamless conversion were also considered. C o n c l u s i o n s . The implementation of EVRS is not merely a technical modernization of the geodetic infrastructure but an integral part of Ukraine’s integration into the European and Euro-Atlantic community. This step will significantly enhance the nation’s defense capabilities through improved geospatial support and contribute to the creation of a unified European spatial data infrastructure, a key strategic goal for Ukraine.